2003
DOI: 10.1021/cm030028k
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sol−Gel Formulations and Surface Treatments for the Development of Pin-Printed Protein Microarrays

Abstract: We report on the development and optimization of a sol-gel-based method for the preparation of protein microarrays that has the potential to allow pin-spotting of active proteins for high throughput multianalyte biosensing and screening of protein-small molecule interactions. Microarrays were printed onto bare and chemically modified surfaces using the commercially available sol-gel precursors tetraethyl orthosilicate and sodium silicate and the newly developed biocompatible sol-gel precursors monosorbitol sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…13 A few studies exist where microarrays of silica gels were directly printed to immobilize proteins [14][15][16][17] and even living cells. 18,19 Nevertheless, it has been shown that pin printing is difficult to perform using traditional sol-gel processing solutions 14 due to severe deposition problems.…”
Section: -12mentioning
confidence: 99%
“…13 A few studies exist where microarrays of silica gels were directly printed to immobilize proteins [14][15][16][17] and even living cells. 18,19 Nevertheless, it has been shown that pin printing is difficult to perform using traditional sol-gel processing solutions 14 due to severe deposition problems.…”
Section: -12mentioning
confidence: 99%
“…The first step toward construction of a viable MetaChip is the optimization of P450 catalysis in sol-gel arrays. Sol-gels offer important advantages for the fabrication of protein-based materials and biocatalytic devices because of their optical transparency, compatibility with various organic moieties, and stability in harsh environments (31)(32)(33). Furthermore, the porosity of sol-gels can be precisely controlled, as can the robustness of the sol-gel structure.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure optimal spot deposition it is highly recommended to use pre-coated slides from a supplier such as Arrayit. In-house coating produces inconsistent surfaces that lead to poor spot reproducibility 13 and, in some cases, may lead to quantification problems. 18 Of equal importance, temperature and humidity affect the "printability" of the materials.…”
Section: Discussionmentioning
confidence: 99%
“…The sol-gel process itself takes place in an aqueous environment at room temperature, and it is the liquid precursor that is printed and then gels to entrap biomolecules within the 3D matrix, allowing for high protein loading 13 as well as entrapment of multiple components within the same microarray element. 13,14 Tailoring of the sol-gel derived material can be done through careful selection of different silica precursors, as well as by altering the aqueous component through use of different buffers (pH, ionic strength), and inclusion of various additives (polymers, small molecules) to achieve an optimal material, the specific nature of which depends on the biomolecule that is entrapped.…”
Section: Introductionmentioning
confidence: 99%